Functionalized silica synthesized by sol-gel process - Nassar, E. J.; Neri, C. R.; Calefi, P. S.; Serra, O. A. (Elsevier B.V., 1999)
This work considers some aspects of the chemistry involved in the preparation and description of silicon oxide functionalized by sol-gel process. In this work we studied the synthesis and measured the properties of silicon oxide functionalized with 3-chloropropyl, through a sol-gel process. Thermogravimetic analysis, infrared spectra, and elemental analyses were measured. The samples were prepared in the following proportions of tetraethylorthosilicate (TEOS): 3-chloropropyl trimethoxisilane molar ratio: 1:0, 1:1, 2:1, 3:1 and 4:1. The thermogravimetric data for the resulting materials established the 'minimum formulae' 2:0, 3:1, 4.1, 7:1 and 11:1, respectively. As expected, the relative amount of water is inversely proportional to the presence of propyl groups. Infrared data show Si-C and -CH2-vibration modes at 1250 to 1280 and 2920 to 2940 cm(-1), respectively. Thermogravimetric data and infrared spectra showed that inorganic polymers contained organic polymers. (C) 1999 Elsevier B.V. B.V. All rights reserved.